Design and Development of Alumni Tracking Information System - iman nasrullah; andri suryadi; Isan nurul Insani (RISTEC : Research in Information Systems and Technology, 2021)
This study aims to produce a web-based alumni tracking information system at SMKN 1 Garut, test the alumni tracking information system based on functional aspects, and see user responses to the alumni tracking information system. This alumni tracking information system was developed using a waterfall model consisting of analysis, design, code, and test. The functional aspect testing through blackbox testing and expert validation was carried out by two experts, then the results were calculated using the matrix feature completeness formula (ISO 9126), while user responses were carried out by giving a questionnaire using a Likert scale to 10 respondents, namely alumni of SMKN 1 Garut. The results of the research are the web-based alumni tracing system at SMKN 1 Garut with the results of blackbox testing and expert validation, namely X is worth 1 then based on the feature completeness matrix (ISO 9126), the alumni tracking system at SMKN 1 Garut is "feasible" in terms of functional aspects. While the results of the calculation for user responses obtained a score of 462 in the range of 400 - 500 score intervals, it is interpreted as "Very Positive".